ESTIMATION OF RESPONSE OF PLATE STRUCTURE SUBJECT TO LOW VELOCTIY IMPACT BY A SOLID OBJECT - YANG, Y.; LAM, N. T. K.; ZHANG, L. (International journal of structural stability and dynamics, 2012)
This paper introduces the use of a two-degree-of-freedom (2DOF) model which comprises two spring-connected lumped masses for analyzing the response behavior of a plate structure to a low velocity impact of a flying solid object. We propose a novel method for calculating the value of the equivalent lumped mass and that of the spring constant which characterizes the 2DOF model. This is an important contribution given that existing calculation methods that are based on results from modal analysis would only be suitable for modeling the impact actions of wind or blast. Analysis involving the use of a 2DOF model is inexpensive and convenient to operate whilst achieving very good accuracies as demonstrated herein. By contrast, modeling impact response behavior by finite element analyses can be very time consuming and labour intensive because of the need to model in detail the impactor in contact with the target.